KAJIAN TERHADAP PENDAPATAN MIGRAN WANITA PEDAGANG SEKTOR INFORMAL DI KOTA DENPASAR - Wijayanti, Ni Nyoman Setya Ari; Marhaeni, A.A.I. N. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018DO - 10.24843/EEB.2018.v07.i04.p01, 2018)
This study aims to analyze;the influence of education level, age, ethnicity, length of marriage age, number of dependents and length of migration to distance migration of informal women migrant traders; the influence of education level, age, ethnicity, age of marriage age, number of dependents, duration of migration and distance of migration to income level of informal female migrant traders;the role of migration spacing in mediating the influence of education level, age, ethnicity, age of marriage, number of dependents and length of migration to income level of informal female migrant traders. The results showed that the level of education, age and number of dependents have a positive and significant effect on the distance of migration of informal women migrant traders in Denpasar City. The duration of migration has a negative and significant effect on the distance of women traders migration. Ethnic and longevity of marriage have no significant effect on migration distance of female migrant traders. The level of education, age, ethnicity, number of dependents and migration spacing have a positive and significant impact on the income of female migrant traders. The duration of the migration has a negative and significant effect on the merchant's income. The age of marriage has no significant effect on income level.